Microfluidic Assays for CD4 T Lymphocyte Counting: A Review - Zhuolun Meng; Hassan Raji; Mahtab Kokabi; Deng Zou; James Chan; Qihao Liu; Ruifeng Zhang; Mehdi Javanmard (Biosensors)
CD4 T lymphocytes play a key role in initiating the adaptive immune response, releasing cytokines that mediate numerous signal transduction pathways across the immune system. Therefore, CD4 T cell counts are widely used as an indicator of overall immunological health. HIV, one of the leading causes of death in the developing world, specifically targets and gradually depletes CD4 cells, making CD4 counts a critical metric for monitoring disease progression. As a result, accurately counting CD4 cells represents a pressing challenge in global healthcare. Flow cytometry remains the gold standard for enumerating CD4 T cells; however, flow cytometers are expensive, difficult to transport, and require skilled medical staff to prepare samples, operate the equipment, and interpret results. This highlights the critical need for novel, rapid, cost-effective, and portable methods of CD4 enumeration that are suitable for deployment in resource-limited countries. This review will survey and analyze emerging research in CD4 counting, with a focus on microfluidic systems, which represent a promising area of investigation.